2022
DOI: 10.55047/jhssb.v1i3.151
|View full text |Cite
|
Sign up to set email alerts
|

The Global Competition in the Digital Society 5.0 Era: The Challenges of the Younger Generation

Abstract: The millennial generation has rapidly taken over the workforce, posing new challenges to global competition in the era of Digital Society 5.0. According to surveys, millennials are technologically savvy. The ability of businesses to consistently enhance performance is contingent on their ability to retain and develop the millennial generation. The development of high-quality human resources (HR) among the millennial generation is a challenge in the era of digital society's global competition. 5.0. The millenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 4 publications
0
21
0
5
Order By: Relevance
“…In fact, what researchers found that the readiness of HR programs to face the Era of Society 5.0 lies in how an educational program integrates information technology with the needs of available human resources. Therefore, this will have an impact on the formation of work and social competencies that will be owned by the younger generation (Apdillah et al, 2022, Ramdani et al, 2020. Well-integrated human resources will form the self-affection and problem-solving competencies of the younger generation in the world of work (Prasetyo et al, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In fact, what researchers found that the readiness of HR programs to face the Era of Society 5.0 lies in how an educational program integrates information technology with the needs of available human resources. Therefore, this will have an impact on the formation of work and social competencies that will be owned by the younger generation (Apdillah et al, 2022, Ramdani et al, 2020. Well-integrated human resources will form the self-affection and problem-solving competencies of the younger generation in the world of work (Prasetyo et al, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Semakin meningkat pengangguran maka akan semakin tidak produktif penduduknya, sehingga penduduk tidak akan mampu memenuhi kebutuhan hidupnya, kebutuhan hidup yang semakin tidak terpenuhi akan meningkatkan tingkat kemiskian (Putra & Arka, 2016). Pendidikan merupakan pionir dalam pembangunan masa depan suatu negara (Apdillah et al, 2022).…”
Section: Pendahuluanunclassified
“…Efektivitas kerja merupakan suatu kondisi yang menyatakan bahwa aktivitas pekerjaan memberikan output sesuai hasil yang diinginkan dengan batasan waktu tertentu, artinya jika output yang dihasilkan semakin mendekati apa yang diinginkan maka semakin tinggi pula efektivitas kerja. Penggunaan aplikasi digital dapat membantu meningkatkan efektivitas kerja karena jika individu yang bersangkutan dapat menguasai teknologi yang digunakan di tempat mereka bekerja, pekerjaan mereka dapat terselesaikan dengan waktu yang lebih singkat dan kendala yang lebih kecil sehingga kapasitas dalam mengerjakan pekerjaan yang diberikan menjadi lebih besar (Apdillah et al, 2022). Seperti yang dikatakan Buchanan et al (2016) bahwa teknologi digital berdampak besar pada tempat kerja dan budaya kerja, penggunaan teknologi digital mempercepat efisiensi kerja dan memperluas tujuan kerja yang ingin dicapai.…”
Section: Pendahuluanunclassified